Targeting Policy for Obesity Prevention: Identifying the Critical Age for Weight Gain in Women - Trevor J. B. Dummer; Sara F. L. Kirk; Tarra L. Penney; Linda Dodds; Louise Parker (Hindawi Limited, 2012)
The obesity epidemic requires the development of prevention policy targeting individuals most likely to benefit. We used self-reported prepregnancy body weight of all women giving birth in Nova Scotia between 1988 and 2006 to define obesity and evaluated socioeconomic, demographic, and temporal trends in obesity using linear regression. There were 172,373 deliveries in this cohort of 110,743 women. Maternal body weight increased significantly by 0.5 kg per year from 1988, and lower income and rural residence were both associated significantly with increasing obesity. We estimated an additional 82,000 overweight or obese women in Nova Scotia in 2010, compared to the number that would be expected from obesity rates of just two decades ago. The critical age for weight gain was identified as being between 20 and 24 years. This age group is an important transition age between adolescence and adulthood when individuals first begin to accept responsibility for food planning, purchasing, and preparation. Policy and public health interventions must target those most at risk, namely, younger women and the socially deprived, whilst tackling the marketing of low-cost energy-dense foods at the expense of healthier options.